Dental therapists' professional role and possible futures within the Malaysian dental workforce / Noor Azhani Zakaria - Noor Azhani, Zakaria (2020)
Introduction: The Malaysian Dental Act 2018 has recently superseded the Dental Act 1971. Under this Act, dental therapists are required to register under the Therapist Division, are allowed to work at the private practice, and treat a person up to the age of 18 years old under direct supervision of dentist. It is important to assess the perceptions among essential stakeholders with regards these changes and how it affects the future dental therapists’ workforce. Objectives: To explore the dental therapist future workforce dynamics across sectors (public-private) in Malaysia. Materials and methods: In Phase 1, three parallel quantitative surveys were conducted using validated self-administered questionnaires. Descriptive, univariate and multivariate analyses were undertaken using SPSS Version 20. The findings in Phase 1 were integrated with relevant data to model the supply, need and demand in a System Dynamic (SD) tool using Vensim Version 7.3.5 from a baseline scenario in 2015 to the projected year of 2030. Four exploratory scenarios were then modelled to explore the implications of working delegation and privatisation within the Malaysian dental workforce. Results: Majority (>90%) of dental therapists had high job motivation with total mean score of 5.9 ± 0.51. Almost one-quarter felt dissatisfied with their pay rate (24.2%) and promotion opportunity (20.5%). 87.6% expected to stay longer in the dental professional and 8.3% of them had the intention to leave the government sector for private sector. Those who foresaw working in the private sector within the next five years were 4.14 times more likely to have the intention to leave than those who preferred to stay in the public. About 71% of parents had a high level of acceptance of dental therapist providing care to their children in the private settings. Younger parents (OR=1.71, 95% CI=1.26,2.52), those who lived in the urban (3.43; OR=1.71, 95% vii CI=1.23,2.36) and of Bumiputera origin (OR=1.92, 95% CI=1.08,3.43) were the predictors of the high acceptance level. Private dentists’ attitude towards the employment of dental therapists at the private settings was low (15.5%) and it is significantly related to their ownership type (p=0.01). The main perceived barriers were cost (69.5%) and perceived lack of knowledge/skills among dental therapists (52%). Finally, SD modelling simulation for baseline scenario shows a potential for oversupply of public dental therapists and private dentists by year 2025 while a potential of undersupply for public dentists throughout the simulation period. The multiple scenarios could range from a shortfall of total public practitioners and surplus of private practitioners by the year 2030. Conclusion: This study highlights the perceptions on the Therapist Division stipulated in the Dental Act 2018 among different stakeholders that can be used as a reference source to the oral health policymakers in managing human resources. Findings portrayed that by increasing dental therapists’ administrative and promotion roles within the private settings has the potential to absorb the potential oversupply at the private sectors in the future and this scenario shows the optimum utilization of the entire dental workforce in Malaysia. Keyword: Dental therapist, private practice, human resource planning, policy changes, computer simulation